Women Entrepreneurship: An Instigation or Obligation - R. Shenbagavalli, Dr.; S. Senthilkumar, Dr. (International Journal of Engineering and Technology, 2018)
The world’s survey 2017 revealed that the most promising avenue of investment, biggest upcoming markets, talent pools and the demographic dividend to be tapped is women’s economic empowerment. In 2016, the entrepreneurial activity had grown to 10 percent and the gender gap contracted to 5 percent. Women initiation has increased to 14 percent but challenges like recognition, financing and sustainability of women led businesses remain unresolved. Inspite of all such challenges its good to record that 14% of Indian businesses are owned by women and out of which 80% are self funded. The study was taken up with the objective of identifying the problems and challenges faced by the women entrepreneurs and solutions to overcome such problems. A sample of 200 women entrepreneurs from rural and urban areas was selected and data is collected and analyzed. The findings revealed that the psychological barriers and the lack of support from the family are the biggest challenge and problems faced by women respondents.